2023
DOI: 10.1186/s12913-022-09011-0
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of removing prescription co-payments on the use of costly health services: a pragmatic randomised controlled trial

Abstract: Objectives To determine whether exempting people (with high health needs and living in areas of high deprivation) from a $5 prescription charge reduces hospital use. Design Two-group parallel prospective randomised controlled trial. Setting People living in the community in various regions of New Zealand. Participants One thousand sixty one people who live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This calculation is based on the assumption of causality, which may not be the case. However, the concurrence of our results with those from experimental 14,15 and other observational studies of different designs 22,23 reinforces the likelihood of there being a causal link between lack of access to medication and increased hospitalisations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This calculation is based on the assumption of causality, which may not be the case. However, the concurrence of our results with those from experimental 14,15 and other observational studies of different designs 22,23 reinforces the likelihood of there being a causal link between lack of access to medication and increased hospitalisations.…”
Section: Discussionsupporting
confidence: 88%
“…A small randomised controlled trial of the provision of free prescriptions in Aotearoa found similar results to ours; participants who were provided with free medications had a lower rate of hospitalisations (all cause, and for selected conditions), although the primary outcomes of hospital length of stay did not meet conventional levels of statistical significance. 14 This experimental design-albeit on a relatively small samplecoupled with benefits seen in an international article 60…”
Section: Discussionmentioning
confidence: 99%
“…18 The government announced its intention to universally remove the $5 prescription charge in July 2023 in the May 2023 budget, 19 informed by the results of the FreeMeds RCT. 15 This qualitative study demonstrates that removal of charges is likely to make a significant difference to the lives of people like our participants: those in areas of high deprivation, with significant health problems. The National/ ACT/New Zealand First coalition government elected later in 2023 said they will reintroduce prescription charges except for people with a SuperGold card or a Community Services card (ie those over 65 or earning a very low income).…”
Section: Discussionmentioning
confidence: 83%
“…that free prescriptions had a significant impact on hospitalisations. 15 This illustrates one of the on-going day-to-day struggles of those who live in poverty. Findings are similar to our earlier paper, 14 suggesting that although the number of people reporting problems affording medicines may have dropped, 8 the reality for some groups has not changed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation